Republic of Mozambique : Staff Report for the 2000 Article IV Consultation and Second Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2001)
Despite the devastating floods, Mozambique has maintained a good record of program implementation under the Poverty Reduction and Growth Facility (PRGF) program. Executive Directors commended this step, and stressed the need to maintain fiscal and monetary stances. They appreciated the authorities' efforts to improve transparency in government operations, functioning of the judiciary, revenue and expenditure management, bank restructuring, and the completion of the review on the code of good practices on fiscal transparency. Directors agreed that the country has successfully completed the second review under the PRGF arrangement.